The Sustainable Production of Carboxymethyl Cellulose from Waste Cotton: A Comprehensive Chemical Analysis - R. Mushkhan,; G.R. Bella, (The Bioscan, 2025)
Waste cotton from the textile industry pollutes the environment and poses health risks. Although waste cotton has high cellulose content, the cellulose insolubility constituted a problem. In the present investigation, waste cotton has been explored as source of cellulose and it was transformed consequently into carboxymethyl cellulose, an anionic, water-soluble derivative of cellulose with numerous uses in different sectors by etherification method. At first, hemicellulose and lignin were eliminated in order to recover cellulose from discarded cotton. Following the extraction of cellulose, monochloroacetic acid and 30% NaOH were used for etherification and alkalization in an isopropanol-ethanol (70:30) medium to generate carboxymethyl cellulose. The yield of produced cellulose and carboxymethyl cellulose was calculated, and they were characterized by Fourier-transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, and thermogravimetric analysis. The yield of cellulose was 97.66%, and carboxymethyl cellulose was 171.05%. The degree of substitution was ascertained using the back titration method. The resulting degree of substitution of CMC was 1.659. It indicated that the synthesised carboxymethyl cellulose was soluble in water. The successful etherification of cellulose became apparent by the occurrence of a new, strong band at 1600 cm-1 (COO-). The amorphous character of carboxymethyl cellulose was confirmed by the loss of several crystalline peaks in cellulose and the development of peaks around 9.4°. The estimated crystallinity index of carboxymethyl cellulose was 30%, a significantly lower figure than the 55.3% crystallinity index for cellulose. Solubility was triggered by lower crystallinity index values. The carboxymethyl cellulose formation was reaffirmed by the rod-like structure. It showed TGA breakdown thermograms at temperatures between 205°C and 401°C. Antimicrobial activity results showed that CMC was not very sensitive towards the microbes. But it was found to be susceptible to Aspergillusniger. In this work, a higher DS and high yield have been attained.